Auto-combustion processed high alumina cement and its implementation as bauxite based low cement castables - Kumar V.; Singh V.K.; Srivastava A.; Kumar P.H. (My University, 2025)
The present work involved solution combustion synthesis of high alumina cements from their metal nitrate precursors, using urea as an organic fuel. Combusted aluminium nitrate, calcium nitrate and urea complexes leads to formation of high alumina cement at temperature as low as 800 °C. The prime cementing phases observed were CA, CA2 and C12A7. The second stage of work evaluates, the role of this high alumina cement (HAC) on bauxite based low cement castables. The effect of micro-fine Cr2O3 and MgO additions on the sinterability and thermo-mechanical strength of these castables was also investigated. Phase identification and microstructural evaluation of the sintered castables confirms spinel and corundum phase formation. Addition of nano structured cements in refractory castables improved the thermo-mechanical properties to a significant extent. © 2014 Elsevier Ltd and Techna Group S.r.l.